2018
DOI: 10.1016/j.nicl.2017.12.032
|View full text |Cite
|
Sign up to set email alerts
|

Performance monitoring in lung cancer patients pre- and post-chemotherapy using fine-grained electrophysiological measures

Abstract: No previous event-related potentials (ERPs) study has explored the error-related negativity (ERN) - an ERP component indexing performance monitoring - associated to cancer and chemotherapy-induced cognitive impairment in a lung cancer population. The aim of this study was to examine differences in performance monitoring in a small-cell lung cancer group (SCLC, C +) 1-month following chemotherapy and two control groups: a non-small cell lung cancer patient group (NSCLC, C −) prior to chemotherapy and a healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 78 publications
1
6
0
Order By: Relevance
“…The analysis of the paired groups showed that decreased volumes were found in more extensive regions, including the frontal, parietal, temporal, occipital, limbic, insular, and partial cerebellar regions. This result is consistent with that of previous studies ( 18 , 35 37 ) and is probably caused by the shorter duration after chemotherapy in the patients of the paired groups, in which the brain regions were temporarily injured and in a recovering state partly ( 21 , 38 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The analysis of the paired groups showed that decreased volumes were found in more extensive regions, including the frontal, parietal, temporal, occipital, limbic, insular, and partial cerebellar regions. This result is consistent with that of previous studies ( 18 , 35 37 ) and is probably caused by the shorter duration after chemotherapy in the patients of the paired groups, in which the brain regions were temporarily injured and in a recovering state partly ( 21 , 38 ).…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, patients with chemotherapy have a greater reduction in temporal lobe volume than those without, and this was associated with a decrease in oral reading recognition scores ( 14 , 19 , 20 ). Hippocampal deformation or volume reduction is another abnormal change in patients receiving chemotherapy, and these changes are related to memory, long education years, poor self-reported cognitive function evaluation, and even a significant increase in inflammatory immune specific interleukin-6 and tumor necrosis factor-α ( 21 24 ). A recent study using gray matter density (GMD) as a parameter indicated that GMD decreased in the left inferior frontal gyrus, right middle frontal gyrus, right fusiform area, and both cerebellums in patients after chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…This problem must be tackled to bring patients back to their premorbid quality of life. Chemobrain is most pronounced in population of patients with breast cancer with a frequency reaching 80% [13], but it also includes lung cancer (30% of patients) [14], Central nervous system (CNS) malignancies [6], testicular cancer [15], and hematologic malignancies [1618], and these deficits appear following treatment with various chemotherapeutic agents that have different mechanisms of action [6]. Pre-treatment cognitive screening did not reveal profound cognitive impairment [19], although some studies point to brain structure abnormalities also in cancer patients not subjected to chemotherapy [2022].…”
Section: Chemobrainmentioning
confidence: 99%
“…Test scores may not fully capture subtle neurophysiological changes that occur after cancer treatment [ 14 ]. Pairing EF tasks, such as the letter n-back (capturing working memory; [ 15 ]) or the Go/No Go (capturing response inhibition; [ 16 ]), with neuroimaging techniques can be used to explore neural activity during EF task performance [ 17 , 18 ]. Functional magnetic resonance imaging (fMRI) is one neuroimaging technique that can help detect differences in neural activity underlying EF, even in the absence of performance or detectable structural changes [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%